Identidades de filhos ouvintes quando os pais são surdos:uma abordagem sociológica sobre o processo de socialização - ANDRADE, Pablo Regis (2011)
This dissertation will discuss the construction of the Identity of hearing children of deaf parents, reflecting on family, socialization and deafness. Firstly we aim to understand who are the family members of those interviewed and how they see their parents, aunts, uncles and grandparents generally considered as part of these groups, a reference for the process of acquisition and the learning of values, beliefs and social rules. Starting with the idea of mediation between individuals and society, we ask what the link would be that allows individuals to see themselves as a family. Contextualized in each timeframes we perceive that family ties are developed within a perspective of loyalty. In the cases researched, the vision that aunts, uncles and grandparents form part of the group that has a direct relation to the need to reach hearing children of deaf parents to communicate orally. Therefore, this method of communication becomes one of the aspects discussed in the second chapter: the language that the children use daily Brazilian Sign Language (LIBRAS) and Portuguese. As a product of a family context, we show how they learn to communicate orally and in sign language as practical sense. These linguistic acquisitions allow those interviewed to mediate between deaf parents and chat we call the outside world, a kind of interpretating responsibility acquired in childhood. After looking at these two questions we will read about how the idea of border identity is dealt with in literature and will analyse parts of interviews that bring to our discussion elements of the way of seeing the world from this conception of being between . In this way, narrative memories about childhood and teenage years of the seven interviewees are used. We seek to understand how they become individuals with their own identities, hearing children of deaf parents, and what is contingent in the process of construction of this way of being and seeing the world. Finally we conclude that identity acquires valve from discourse for people who live between two different worlds.